Phosphoinositides: Roles in the Development of Microglial-Mediated Neuroinflammation and Neurodegeneration - Ernest James Phillips, Thomas; Maguire, Emily (Frontiers in Cellular Neuroscience, 2021)
Microglia are increasingly recognized as vital players in the pathology of a variety of neurodegenerative conditions including Alzheimer’s (AD) and Parkinson’s (PD) disease. While microglia have a protective role in the brain their dysfunction can lead to neuroinflammation and contributes to disease progression. In addition, a growing body of literature highlights the seven phosphoinositides, or PIPs, as key players in the regulation of microglial-mediated neuroinflammation. These small signaling lipids are phosphorylated derivates of phosphatidylinositol, are enriched in the brain, and have well established roles in both homeostasis and disease. Disrupted PIP levels and signaling has been detected in a variety of dementias. Moreover, many known AD disease modifiers identified via genetic studies are expressed in microglia and are involved in phospholipid metabolism. One of these, the enzyme PLCγ2 that hydrolyses the PIP species PI(4,5)P2, displays altered expression in AD and PD, and is currently being investigated as a potential therapeutic target. Perhaps unsurprisingly, neurodegenerative conditions exhibiting PIP dyshomeostasis also tend to show alterations in aspects of microglial function regulated by these lipids. In particular, phosphoinositides regulate the activities of proteins and enzymes required for endocytosis, toll-like receptor signaling, purinergic signaling, chemotaxis, and migration, all of which are affected in a variety of neurodegenerative conditions. These functions are crucial to allow microglia to adequately survey the brain and respond appropriately to invading pathogens and other abnormalities, including misfolded proteins. AD and PD therapies are being developed to target many of the above pathways, and although not yet investigated, simultaneous PIP manipulation might enhance beneficial effects observed. Currently only limited therapeutics are available for dementia, and although these show some benefits for symptom severity and progression, they are far from curative. Given the importance of microglia and PIPs in dementia development, this review summarizes current research and asks whether we can exploit this information to design more targeted, or perhaps combined, dementia therapeutics. More work is needed to fully characterize the pathways discussed in this review, but given the strength of the current literature, insights in this area could be invaluable for the future of neurodegenerative disease research.